Peran Bank dalam Pembiayaan UMKM dan Dampaknya terhadap Perekonomian Lokal - Alea Casta Supriyadi; Kayla Dora Iftachullah; Cindy Rahmawati Putri; Lintang Ayu Timuja; Nazma Auliya Maulidina (Pusat Riset dan Inovasi Nasional, 2024)
The role of banks in financing Micro, Small, and Medium Enterprises (MSMEs) and its impact on local economies is a crucial area of study in contemporary financial research. This study delves into the multifaceted relationship between banks, MSMEs, and local economies, employing a quantitative methodology coupled with a literature review technique. Through meticulous examination of existing literature and quantitative analysis of secondary data, this research aims to elucidate the extent of banks' involvement in MSME financing and its repercussions on local economic dynamics. By scrutinizing various financial reports, government publications, and academic sources, the study will discern patterns and trends in MSME financing patterns, evaluate the efficacy of banking policies supporting MSMEs, and assess the consequential effects on local economies, including growth indicators like employment rates and income levels. The findings are anticipated to offer valuable insights for banks, policymakers, and stakeholders, guiding them towards more informed decision-making processes and strategies to foster sustainable MSME growth and bolster local economic resilience.